A Phase 1 study of GDC‐0134, a dual leucine zipper kinase inhibitor, in ALS. Issue 1 (10th January 2022) - Katz, Jonathan S.; Rothstein, Jeffrey D.; Cudkowicz, Merit E.; Genge, Angela; Oskarsson, Björn; Hains, Avis B.; Chen, Chen; Galanter, Joshua; Burgess, Braydon L.; Cho, William; Kerchner, Geoffrey A.; Yeh, Felix L.; et al.
Abstract: Objective: Dual leucine zipper kinase (DLK), which regulates the c‐Jun N‐terminal kinase pathway involved in axon degeneration and apoptosis following neuronal injury, is a potential therapeutic target in amyotrophic lateral sclerosis (ALS). This first‐in‐human study investigated safety, tolerability, and pharmacokinetics (PK) of oral GDC‐0134, a small‐molecule DLK inhibitor. Plasma neurofilament light chain (NFL) levels were explored in GDC‐0134‐treated ALS patients and DLK conditional knockout (cKO) mice. Methods: The study included placebo‐controlled, single and multiple ascending‐dose (SAD; MAD) stages, and an open‐label safety expansion (OLE) with adaptive dosing for up to 48 weeks. Results: Forty‐nine patients were enrolled. GDC‐0134 (up to 1200 mg daily) was well tolerated in the SAD and MAD stages, with no serious adverse events (SAEs). In the OLE, three study drug‐related SAEs occurred: thrombocytopenia, dysesthesia (both Grade 3), and optic ischemic neuropathy (Grade 4); Grade ≤2 sensory neurological AEs led to dose reductions/discontinuations. GDC‐0134 exposure was dose‐proportional (median half‐life = 84 h). Patients showed GDC‐0134 exposure‐dependent plasma NFL elevations; DLK cKO mice also exhibited plasma NFL compared to wild‐type littermates. Interpretation: This trial characterized GDC‐0134 safety and PK, but no adequately tolerated dose was identified. NFL elevations in GDC‐0134‐treated patients and DLK cKO mice raised questions about interpretation of biomarkers affected by both disease and on‐target drug effects. The safety profile of GDC‐0134 was considered unacceptable and led to discontinuation of further drug development for ALS. Further work is necessary to understand relationships between neuroprotective and potentially therapeutic effects of DLK knockout/inhibition and NFL changes in patients with ALS.